INFORMATIVE-COMMUNICATION TECHNOLOGIES AS MEAN OF FORMING OF THE SELF-EDUCATIONAL COMPETENCE OF FUTURE PRIMARY SCHOOL TEACHERS - N. Voropay (Ìнформаційні технології в освіті, 2013)
The article opens the question of the use of informative-communicative technologies in process of formation of the selfeducational competence in teachers of primary school.